Large variability in drought survival among Urochloa spp. cultivars. (30th July 2018) - Beloni, Tatiane; Santos, Patricia Menezes; Rovadoscki, Gregori Alberto; Balachowski, Jennifer; Volaire, Florence
Abstract: The Urochloa spp. cultivars are largely used for forage production in tropical and humid subtropical zones in Brazil. However, in areas of transition to drier zones, the persistence of Urochloa cultivars may be jeopardized by severe drought. We aimed to quantify and describe variability in growth potential under irrigation as well as dehydration tolerance and avoidance in cultivars under severe drought of Urochloa C4 species ( Urochloa brizantha, cvs. Marandu and BRS Paiaguás and Urochloa decumbens cv. Basilisk), which were hypothesized to be less dehydration tolerant than a Mediterranean C3 species ( Dactylis glomerata L. cv. Medly). Two experiments were carried out in a controlled environment—one in pots and one in long tubes—each under irrigation and drought successively. Marandu and Basilisk cultivars produced double the aerial and root biomass of cv. BRS Paiaguás. Their root systems were also deeper conferring them higher dehydration avoidance; however, they exhibited lower dehydration tolerance under severe drought. Conversely, cv. BRS Paiaguás was less productive, more dehydration tolerant and, therefore, able to survive at lower soil moisture, similar to the drought tolerant cv. Medly. The BRS Paiaguás cultivar may show sward persistence where extreme drought is experienced, but results should be confirmed under field conditions.